(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2018)
Adsorption of anionic surfactant sodium dodecyl sulfate and cationic surfactant cetyltrimethylammonium bromide from aqueous solution on bentonite was studied. A series of batch experiments were performed to obtain sorption isotherms of surfactants on bentonite. Furthermore, the isotherm parameters were calculated. Other factors influencing the adsorption effectiveness (contact time, adsorbent amount and initial surfactant concentration) were also determined.